Analysis of the Operational Efficiency of Public Hospitals in Tianjin City based on a Three-Stage Data Envelopment Analysis Model - Zhao, Shuai; He, Lisha; Fu, Xiao; Ma, Weishu (Transactions on Economics, Business and Management Research, 2024)
The purpose is to analyze the operational efficiency of 132 public hospitals in Tianjin in 2021, providing reference for them to fully play the role of "leading institutions" and optimize resource allocation. We constructed an evaluation index system with multiple inputs, outputs, and environmental variables and utilized a three-stage DEA model to assess efficiency by removing the influence of random errors and environmental factors. The average comprehensive technical efficiency, pure technical efficiency, and scale efficiency of public hospitals were 0.865, 0.989, and 0.875, respectively. Among them, seven districts, including Heping, Hedong, and Hexi, had a comprehensive technical efficiency of 1. Among the remaining nine districts, except for Baodi, the rest showed an increasing trend in scale efficiency. Public hospitals in Tianjin City exhibit high operational efficiency, but significant variations exist among different districts, leading to uneven development. The main reason for this disparity is the presence of scale inefficiency. It is recommended to prioritize resource optimization and address the shortcomings that hinder efficiency improvement in a targeted manner. Emphasizing the "triple integration" of service capacity, efficiency, and quality in public hospitals is essential to maximize both social and economic benefits."